2009
DOI: 10.1093/ndt/gfp506
|View full text |Cite
|
Sign up to set email alerts
|

Improved growth and cardiovascular risk after late steroid withdrawal: 2-year results of a prospective, randomised trial in paediatric renal transplantation

Abstract: Late steroid withdrawal in selected CsA- and MMF-treated paediatric kidney transplant recipients improves growth, mitigates cardiovascular risk factors and reduces the prevalence of the metabolic syndrome, at no increased risk of acute rejection or unstable graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 25 publications
7
49
0
2
Order By: Relevance
“…This is reported especially for young children, who are known to have the best growth rates even with corticosteroid-based treatment regiments. In the multicenter study of Sarwal et al [3], the subgroup of recipients <5 years of age showed improvement in height SDS (1.07 ± 1.14 within 3 years) with complete avoidance of corticosteroids when compared with patients on steroid-based treatment (0.43 ± 1.15). Late selective withdrawal of corticosteroids in the randomized study of Höcker et al [2] improved height SDS by +0.6 ± 0.1 within 2 years compared with −0.2 ± 0.1 in controls.…”
Section: Growth After Steroid Avoidance For Renal Transplantationmentioning
confidence: 93%
See 3 more Smart Citations
“…This is reported especially for young children, who are known to have the best growth rates even with corticosteroid-based treatment regiments. In the multicenter study of Sarwal et al [3], the subgroup of recipients <5 years of age showed improvement in height SDS (1.07 ± 1.14 within 3 years) with complete avoidance of corticosteroids when compared with patients on steroid-based treatment (0.43 ± 1.15). Late selective withdrawal of corticosteroids in the randomized study of Höcker et al [2] improved height SDS by +0.6 ± 0.1 within 2 years compared with −0.2 ± 0.1 in controls.…”
Section: Growth After Steroid Avoidance For Renal Transplantationmentioning
confidence: 93%
“…Complete avoidance [3] or selective withdrawal [2] of corticosteroids leads without doubt to significant improvement in growth. This is reported especially for young children, who are known to have the best growth rates even with corticosteroid-based treatment regiments.…”
Section: Growth After Steroid Avoidance For Renal Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unsurprising, therefore, to see that the prevalence of the metabolic syndrome in children increases following transplantation, affecting between 20 and 40 % of individuals in the first 1-2 years post-transplantation, particularly with prolonged corticosteroid use [50,51]. It is obesity and its influence on the development of the cardiovascular risk factors comprising the metabolic syndrome that are the central components of the elevated incidence of cardiovascular mortality in paediatric renal transplantation.…”
Section: Cardiovascular Riskmentioning
confidence: 99%